Species Diversity of Marine Planktonic Diatoms around Chang Islands, Trat Province - Kesorn Teanpisut; Sunan Patarajinda (Agriculture and Natural Resources, 2007)
In March 2003, the marine planktonic diatoms were collected from 27 stations around Chang Islands, Trat Province in the Gulf of Thailand. Two types of the plankton net were used as filtering 100 litres of seawater through 20 μm mesh size and obliquely towing 70 μm mesh size at 2 meters above the seafloor. The diatoms was made by using light microscope (LM) and scanning electron microscope (SEM). The results showed that at least 70 genera and 140 species were identified under the Order of Biddulphiales (centric diatoms, including 38 genera and 93 species) and Bacillariales (pennate diatoms, including 32 genera and 47 species). From this study, species Stictocyclus varicus A. Mann was remarked as a first record in Thai’s waters, and Asteromphalus robustus Castracane was remarked as a first record in the Gulf of Thailand.